Generation of XPA p.Arg228T mutant LUMCi004-A cell line for modeling Xeroderma pigmentosum group A - Halida P. Widyastuti; Babet van der Vaart; Spyridon T. Pachis; Christian Freund; Xavier Gidrol; Karine Raymond (Stem Cell Research)
Xeroderma pigmentosum group A (XPA) is an inherited skin disorder characterized by sensitivity to ultraviolet radiation. In Maghrebi patients, a homozygous mutation in exon 6 of the XPA gene (c.682C>T) results in the introduction of a premature termination codon. Using CRISPR/Cas9-mediated gene editing, this mutation was introduced into the well-characterized LUMCi004-A line. The resulting hiPSC line showed typical morphology, expressed markers of the undifferentiated state, was able to differentiate into the three germ layers in vitro and displayed a normal karyotype. When paired with its isogenic counterpart, this line represents a valuable resource to model the disease.